Method for improving toughness of ultra-high performance concrete and application thereof

By modifying the steel fibers with hydrophilic organic substances, the bonding strength with ultra-high performance concrete matrix is ​​enhanced, and the problem of insufficient bonding between steel fibers and concrete matrix in existing ultra-high performance concrete is solved, and the effect of improving bending resistance and toughness is achieved.

CN119774936APending Publication Date: 2025-04-08CHONGQING JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510042509.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Among existing ultra-high performance concrete, the bonding between steel fibers and concrete substrates is insufficient, resulting in the inadequate use of its bending resistance and toughness.

Method used

The steel fiber is modified with hydrophilic organic substances to enhance its bonding strength with ultra-high performance concrete matrix. The specific steps include rinsing the steel fibers with ultrapure water and anhydrous ethanol, then soaking them with a hydrophilic organic substance solution and sonicating them, and finally stirring the modified steel fibers with cement, fly ash and other materials evenly.

Benefits of technology

It significantly improves the bending resistance and toughness of ultra-high performance concrete, extends its service life, and is simple to operate, low cost and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774936A_ABST
    Figure CN119774936A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving toughness of ultra-high performance concrete and application of the method, and belongs to the technical field of ultra-high performance concrete. According to the method provided by the invention, the bonding strength of the steel fiber and the matrix interface of the ultra-high-performance concrete is enhanced while the surface and mechanical properties of the steel fiber are not damaged, so that the bending resistance and toughness of the prepared ultra-high-performance concrete are remarkably improved, and the application range of the ultra-high-performance concrete is widened. The bonding strength and the service life of the steel fiber of the ultra-high performance concrete and an ultra-high performance concrete matrix interface are prolonged; the provided method is simple and easy to operate, low in cost and good in toughening effect, and the mechanical strength of the steel fibers is not affected; the used raw materials are non-toxic or very low in toxicity, toxic and harmful substances are not generated in the process, and the method is environment-friendly and suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ultra-high performance concrete, and in particular to a method for improving the toughness of ultra-high performance concrete and an application thereof. Background Art

[0002] Ultra-high performance concrete (UHPC) is an advanced cementitious composite material with excellent compressive strength, high toughness and durability. The bonding between steel fiber and UHPC matrix determines the flexural performance and toughness of UHPC. However, the smooth surface of steel fiber leads to poor bonding between fiber and UHPC matrix, so that the ductility and tensile strength of UHPC are not fully utilized. Therefore, it is very necessary to improve the bonding between steel fiber and UHPC matrix in order to improve the flexural performance of UHPC. At present, some studies have been conducted to enhance the bonding strength between fiber and UHPC by changing the shape of steel fiber to enhance the mechanical interlocking between fiber and matrix, but the use cost of deformed fiber will increase compared with straight fiber; in addition, the use of a large number of deformed fibers will produce splitting cracks during the drawing process. There are also studies on plasma, flame and strong acid and alkali treatment of fiber surface, but the above treatment methods are not only complicated to operate and cannot be used on a large area, but also affect the mechanical strength of the fiber itself. The addition of nanomaterials can also effectively improve its flexural performance, but it also faces problems such as high cost and difficulty in dispersion. Summary of the invention

[0003] The purpose of the present invention is to provide a method for improving the toughness of ultra-high performance concrete and its application, so as to provide a method with low cost, simple operation and good effect to improve the bonding performance between steel fiber and ultra-high performance concrete matrix, thereby improving the compressive strength and toughness of ultra-high performance concrete, broadening the scope of use of ultra-high performance concrete, and extending the service life of ultra-high performance concrete.

[0004] To achieve the above object, the present invention provides a method for improving the toughness of ultra-high performance concrete, comprising the following steps: S1. Modifying steel fibers with hydrophilic organic substances; S2. Dry the obtained modified steel fiber, add the modified steel fiber, cement, fly ash, silica fume and river sand into a mixer according to proportion, stir and mix for 2-5 minutes, then add high-efficiency water reducing agent and water and continue stirring for 2-5 minutes to obtain ultra-high performance concrete slurry, which can be maintained normally after laying.

[0005] Preferably, the hydrophilic organic substance in S1 is an organic substance having a hydrophilic functional group and / or viscosity, and has a relative molecular mass of 100-60000.

[0006] Preferably, the hydrophilic organic substance is polyvinyl pyrrolidone, polyvinylidene fluoride or chitosan; when the hydrophilic organic substance is chitosan, adipic acid is added at a final concentration of 0.1%.

[0007] Preferably, the method of modifying the steel fiber with a hydrophilic organic substance is: S11, washing or soaking the steel fiber with ultrapure water and anhydrous ethanol in sequence to remove impurities on the surface of the steel fiber; S12, drying the cleaned steel fiber at 40-60° C. for 3-6 hours; S13, adding the hydrophilic organic substance to anhydrous ethanol, ultrasonically dispersing for 10 minutes, and then stirring for 30 minutes to prepare a solution; S14, placing the steel fiber dried in step S12 in the solution prepared in step S13, ultrasonically treating for 5-15 minutes and then soaking for 15-90 minutes.

[0008] Preferably, the concentration of the hydrophilic organic substance in S13 is 0.1-5%, and the stirring speed is 100-300 rpm.

[0009] Preferably, the ultrasonic power in steps S13 and S14 is 200-1200w.

[0010] Preferably, the modified steel fiber in S2 is dried at 45-60° C. for 1-3 hours; the diameter of the modified steel fiber is 0.2 mm, the length is 2 mm, and the addition amount of the modified steel fiber is 1-3%.

[0011] Preferably, the high-efficiency water reducing agent in step S2 is a water reducing agent having a water reducing effect of 60% or more, and is a polycarboxylic acid-based high-efficiency water reducing agent.

[0012] Preferably, in step S2, 1 cubic meter of ultra-high performance concrete slurry is composed of 818.14-850.726 kg of cement, 205.016-213.182 kg of fly ash, 205.016-213.182 kg of silica fume, 899.954-935.799 kg of river sand, 37.538-39.033 kg of high-efficiency water reducing agent and 198.279-167.143 kg of water; the stirring speed of the mixer is 90-110 rpm.

[0013] An application of the method for improving the toughness of ultra-high performance concrete as described above in the preparation of ultra-high performance concrete.

[0014] Therefore, the present invention provides a method for improving the toughness of ultra-high performance concrete and its application, and its specific technical effects are as follows: (1) The method provided by the present invention enhances the bonding strength between the steel fiber and the ultra-high performance concrete matrix interface without damaging the surface and mechanical properties of the steel fiber, thereby significantly improving the bending resistance and toughness of the prepared ultra-high performance concrete, which is of great significance for expanding the scope of use of ultra-high performance concrete and extending the bonding strength and service life of the interface between the steel fiber of the ultra-high performance concrete and the ultra-high performance concrete matrix; (2) The method provided by the present invention is simple and easy to operate, has low cost, does not affect the mechanical strength of the steel fiber itself, and has a good toughening effect; the raw materials used are non-toxic or have very low toxicity, no toxic or harmful substances are generated during the process, and it is environmentally friendly and suitable for popularization and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.

[0016] Figure 1 This is a steel fiber modification flow chart provided by the present invention; Figure 2 is a scanning electron microscope image of the control group steel fiber (a) and the steel fiber modified with 3% PVP (b) in Example 1 of the present invention; Figure 3 The bending performance test results of concrete prepared by using the steel fibers of the control group and the treatment group in Example 1 of the present invention; Figure 4 These are scanning electron microscope images of the steel fibers of the control group (a) and 3% PVP modified (b) after the bending performance test in Example 1 of the present invention; Figure 5 These are scanning electron microscope images of the modified steel fibers of the control group (a, b), the 0.5% CTS modified steel fibers (c), and the 1% CTS modified steel fibers (d) in Example 2 of the present invention; Figure 6 The bending performance test results of concrete prepared by using the steel fibers of the control group and the treatment group in Example 2 of the present invention; Figure 7 It is a scanning electron microscope photograph of the steel fiber after the bending performance test in Example 2 of the present invention; wherein parts a, b, e and f are control group steel fibers, parts c and g are 0.5% CTS modified steel fibers, and parts d and h are 1% CTS modified steel fibers. DETAILED DESCRIPTION

[0017] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0018] In order to make the purpose, technical scheme and advantages of the present application clearer, more thorough and more complete, the technical scheme of the present invention is clearly and completely described below through the accompanying drawings and examples. The following detailed descriptions are all descriptions of the embodiments, and are intended to provide further detailed descriptions of the present invention. Unless otherwise specified, all technical terms used in the present invention have the same meaning as those generally understood by those skilled in the art to which the present application belongs.

[0019] The instruments, equipment, reagents and materials used in the examples were obtained from commercial sources. The steel fibers used in the examples were straight fibers or end-hook fibers, with a fiber diameter of 0.2 mm and a length of 2 mm. The strength of the cement used was 52.5 and the density was 3150 kg / m 3 , particle size is 2-50μm; silica fume density is 2200kg / m 3 , particle size is 15-245μm; river sand density is 2700kg / m 3 , particle size is 0.1-3mm; fly ash density is 2700kg / m 3 , the particle size is 3-26 μm. The experimental steps and methods not described in detail in the examples are all conventional methods in the art.

[0020] The method for improving the toughness of ultra-high performance concrete provided by the present invention first modifies the steel fiber (the flow chart is as follows Figure 1 As shown in the figure, the modified steel fiber is then mixed with cement, fly ash, silica fume and river sand in a certain proportion, poured into a mold and then subjected to conventional curing. There is no need to perform etching or other treatments on the surface of the steel fiber, and the surface and mechanical properties of the steel fiber are not damaged.

[0021] Embodiment 1 The steps of preparing an ultra-high performance concrete are as follows: S11. Accurately weigh the steel fiber (straight fiber), rinse it with deionized water and then rinse it with anhydrous ethanol for 3 times to remove impurities on the surface of the steel fiber, and place the cleaned steel fiber in a blast drying oven at 45°C for 6 hours. After the steel fiber cools to room temperature, weigh the dried steel fiber, and weigh a total of 4 portions, each 3532.5g.

[0022] S12. Weigh 100g, 300g and 500g of polyvinylpyrrolidone (PVP) respectively, add them into 10000g, 9700g and 9500g of anhydrous ethanol respectively, disperse them ultrasonically for 10 minutes (ultrasonic power is 500w), and then stir them magnetically for 30 minutes at a stirring speed of 200r / min to obtain PVP solutions with mass fractions of 1%, 3% and 5% respectively.

[0023] S13, the steel fiber dried in step S11 is placed in the PVP solution with a mass fraction of 1%, 3% and 5% prepared in step S12, preferably the PVP solution completely covers the steel fiber, and ultrasonically treated with an ultrasonic cleaner for 10 minutes to fully mix and contact the steel fiber with the solution, and then soaked at room temperature for 90 minutes, removed and water controlled, placed in a blast drying oven at 60°C for 6 hours, and recorded as the treatment group. The remaining portion of steel fiber dried in step S11 is recorded as the control group (0%).

[0024] The scanning electron microscopy (SEM) images of the control group steel fibers and the steel fibers modified with 3% PVP are shown in Figure 2. Figure 2 As shown in Figure 1, part a is the control group steel fiber. It can be seen that the original fiber has many grooves due to the extrusion molding process. In contrast, the grooves on the fiber surface modified by 3% PVP solution are significantly reduced (part b), indicating that PVP successfully coated the fiber surface, and the fiber surface coating is uniform and dense.

[0025] S14, accurately weigh 1906.347g cement, 477.708g fly ash, 477.708g silica fume and 2096.981g river sand, add them to the mixer and stir for 5 minutes to mix the dry materials evenly. Then add 87.468g high-efficiency water reducer (component is polycarboxylic acid) and 383.512g water and continue stirring for 5 minutes to obtain slurry, then add 353.25g modified steel fiber obtained in step S13 and continue stirring for 5 minutes, then pour it into a 100mm×100m×400mm steel mold, and conventionally cure for 28 days, which is recorded as the treatment group. The slurry of the control group steel fiber in step S13 with an equal amount of addition is the control group, recorded as 0% PVP, and the preparation method is exactly the same as the treatment group.

[0026] A four-point bending test was carried out using a pressure testing machine to test the bending properties of concrete prepared with steel fibers in the control group and the treatment group. The results are as follows: Figure 3 As shown in the figure, the bending loads of steel fibers modified with 0%, 1%, 3% and 5% PVP are 55.67 kN, 59.49 kN, 69.22 kN and 78.36 kN respectively. Compared with the control group, the bending load of the modified group is increased by 40.76%.

[0027] The SEM images of the steel fibers after the experiment are as follows: Figure 4 As shown, part a is the control group steel fiber, and part b is the 3% PVP modified steel fiber. It can be seen that the surface of the steel fiber modified with 3% PVP has more matrix fragments than the control group, which once again proves that the modified fiber enhances the bonding strength of the interface with the concrete matrix.

[0028] Embodiment 2 An ultra-high performance concrete slurry is prepared, and the specific steps are as follows: S21. Accurately weigh the steel fiber (end hook fiber), rinse it twice with deionized water and then rinse it three times with anhydrous ethanol to remove impurities on the surface of the steel fiber, and place the cleaned steel fiber in a blast drying oven at 60°C for 4 hours. After the steel fiber cools to room temperature, weigh the dried steel fiber, weighing a total of 3 portions, each 529.85g.

[0029] S22. Weigh 50g and 100g of chitosan respectively, add them into 950g and 900g of anhydrous ethanol respectively, and ultrasonically disperse them for 10 minutes (ultrasonic power is 200w), followed by magnetic stirring for 30 minutes at a stirring speed of 100r / min, to obtain chitosan solutions with mass fractions of 0.5% and 1%, respectively.

[0030] S23, the steel fibers dried in step S21 are placed in a sodium hydroxide solution with a mass fraction of 10% for 1 hour to achieve surface hydroxylation of the steel fibers. Then, the steel fibers are rinsed with anhydrous ethanol and deionized water for 3 times respectively, and after the water is controlled, the steel fibers are placed in a blast drying oven at 60° C. and dried to constant weight.

[0031] S24. Take one portion of the steel fiber dried in step S23 as a control group, and add the other two portions into the chitosan solutions with mass fractions of 0.5% and 1% prepared in step S22, respectively, so that the chitosan solution completely covers the steel fiber. Use an ultrasonic cleaner to ultrasonically treat for 10 minutes to allow the steel fiber to be fully mixed and contacted with the solution, then soak at room temperature for 3 hours, remove and control the water, place in a forced air drying oven and dry at 60°C for 6 hours, and record as the treatment group.

[0032] The scanning electron microscopy (SEM) images of the control steel fibers and the steel fibers modified with 0.5% and 1% CTS are shown in Figure 2. Figure 5 As shown, parts a and b are the control group, part c is the 0.5% PVP modified steel fiber, and part d is the 1% PVP modified steel fiber. It can be seen that a layer of substance is attached to the surface of the modified steel fiber.

[0033] S24, accurately weigh 1840.815g cement, 461.287g fly ash, 461.287g silica fume, and 2024.896g river sand, add them to a mixer and stir for 5 minutes to mix the dry materials evenly. Then add 84.461g high-efficiency water reducer (component is polycarboxylic acid) and 446.127g water and continue stirring for 3 minutes to obtain slurry, then add 529.85g steel fiber obtained in step S23 and continue stirring for 5 minutes, then pour into a 100mm×100m×400mm steel mold, and perform conventional curing for 28 days.

[0034] The four-point bending test method was used to test the bending properties of the concrete prepared with steel fibers in the control group and the treatment group. The results are as follows: Figure 6 As shown in the figure, the bending loads of steel fibers modified with 0% CTS, 0.5% CTS and 1% CTS are 54.55 kN, 66.29 kN and 80.22 kN respectively. The bending load of the treated group is increased by 47.06% compared with the control group.

[0035] The SEM image of the steel fiber surface after the bending performance test is as follows: Figure 7 As shown, part a, part b, part e and part f are control groups, part c and part g are 0.5% CTS modified steel fibers, and part d and part h are 1% CTS modified steel fibers. It can be seen that after the bending performance test, the steel fiber surface of the steel fiber that has not been modified by CTS is smooth and there are almost no concrete matrix fragments. After CTS modification, a large number of concrete matrix fragments are attached to the surface of the steel fiber, indicating that the hydrophilicity of the steel fiber modified by CTS is enhanced, which improves the bonding strength of the interface between the steel fiber and the matrix.

[0036] Therefore, the method provided by the present invention enhances the bonding strength between the steel fiber and the ultra-high performance concrete matrix interface without damaging the surface and mechanical properties of the steel fiber, thereby significantly improving the bending resistance and toughness of the prepared ultra-high performance concrete, which is of great significance for expanding the scope of use of ultra-high performance concrete and extending the bonding strength and service life of the interface between the steel fiber of ultra-high performance concrete and the ultra-high performance concrete matrix; the provided method is simple and easy to operate, low in cost, does not affect the mechanical strength of the steel fiber itself, and has a good toughening effect; the raw materials used are non-toxic or have very low toxicity, no toxic and harmful substances are generated during the process, and the method is environmentally friendly and suitable for popularization and use.

[0037] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for improving the toughness of ultra-high performance concrete, characterized in that: Here are the steps: S1. Modifying steel fibers with hydrophilic organic substances; S2. Dry the obtained modified steel fiber, add the modified steel fiber, cement, fly ash, silica fume and river sand into a mixer according to proportion, stir and mix for 2-5 minutes, then add high-efficiency water reducing agent and water and continue stirring for 2-5 minutes to obtain ultra-high performance concrete slurry, which can be maintained normally after laying.

2. A method for improving the toughness of ultra-high performance concrete according to claim 1, characterized in that: The hydrophilic organic substance in S1 is an organic substance having a hydrophilic functional group and / or viscosity, and has a relative molecular mass of 100-60000.

3. A method for improving the toughness of ultra-high performance concrete according to claim 2, characterized in that: The hydrophilic organic substance is polyvinyl pyrrolidone, polyvinylidene fluoride or chitosan; when the hydrophilic organic substance is chitosan, adipic acid is added with a final concentration of 0.1%.

4. A method for improving the toughness of ultra-high performance concrete according to claim 1, characterized in that: The method of modifying steel fiber with hydrophilic organic substances is as follows: S11, washing or soaking the steel fiber with ultrapure water and anhydrous ethanol in sequence to remove impurities on the surface of the steel fiber; S12, drying the cleaned steel fiber at 40-60° C. for 3-6 hours; S13, adding the hydrophilic organic substance to anhydrous ethanol, ultrasonically dispersing for 10 minutes, and then stirring for 30 minutes to prepare a solution; S14, placing the steel fiber dried in step S12 in the solution prepared in step S13, ultrasonically treating for 5-15 minutes and then soaking for 15-90 minutes.

5. A method for improving the toughness of ultra-high performance concrete according to claim 4, characterized in that: The concentration of the hydrophilic organic substance in S13 is 0.1-5%, and the stirring speed is 100-300 rpm.

6. A method for improving the toughness of ultra-high performance concrete according to claim 4, characterized in that: The ultrasonic power in steps S13 and S14 is 200-1200w.

7. The method for improving the toughness of ultra-high performance concrete according to claim 1, characterized in that: The modified steel fiber in S2 is dried at 45-60° C. for 1-3 hours; the diameter of the modified steel fiber is 0.2 mm, the length is 2 mm, and the addition amount of the modified steel fiber is 1-3%.

8. The method for improving the toughness of ultra-high performance concrete according to claim 1, characterized in that: The high-efficiency water reducing agent in step S2 is a water reducing agent with a water reducing effect of more than 60%, and is a polycarboxylic acid-based high-efficiency water reducing agent.

9. The method for improving the toughness of ultra-high performance concrete according to claim 1, characterized in that: In step S2, 1 cubic meter of ultra-high performance concrete slurry is composed of 818.14-850.726 kg of cement, 205.016-213.182 kg of fly ash, 205.016-213.182 kg of silica fume, 899.954-935.799 kg of river sand, 37.538-39.033 kg of high-efficiency water reducing agent and 198.279-167.143 kg of water; the stirring speed of the mixer is 90-110 rpm.

10. Use of the method for improving the toughness of ultra-high performance concrete according to any one of claims 1 to 9 in the preparation of ultra-high performance concrete.